2020
DOI: 10.1002/pmic.202000006
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Changes in Sorafenib‐Treated Hepatocellular Carcinoma Cells Suggests Involvement of Phospho‐Regulated Signaling in Ferroptosis Induction

Abstract: Ferroptosis is a form of regulated, non-apoptotic cell death characterized by excessive lipid peroxidation that can be triggered by inhibition of the cystine-glutamate antiporter, system X c − . Sorafenib, an FDA-approved multi-kinase inhibitor drug that is used for treatment of hepatocellular carcinoma (HCC), has been shown to induce ferroptosis. Protein phosphorylation changes upon sorafenib treatment have been previously reported in patient studies and in cell culture. However, early phosphorylation changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Increasing evidences have showed that ferroptosis acts important roles in HCC treatment. Ferroptosis is a vital part of mechanisms for sorafenib, which is rst line therapy for HCC [29]. LDL-DHA nanoparticles, a potential new drug for HCC, cause ferroptosis in HCC tissues [30].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences have showed that ferroptosis acts important roles in HCC treatment. Ferroptosis is a vital part of mechanisms for sorafenib, which is rst line therapy for HCC [29]. LDL-DHA nanoparticles, a potential new drug for HCC, cause ferroptosis in HCC tissues [30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another publication contributed to a better understanding of the mode of ferroptosis induction in HCC cells by sorafenib. The authors found that sorafenib treatment for 60 min resulted in changes at phosphorylation sites of proteins that are involved in iron homeostasis and of proteins that are part of ferroptosis-related pathways [ 83 ]. However, there are also reports that sorafenib fails to trigger ferroptosis in different cancer cell lines including HCC [ 93 ], which might indicate cell line-specific effects, other (molecular) factors that contribute to the sensitivity of sorafenib-induced ferroptosis or both.…”
Section: The Pharmacological Induction Of Ferroptosis In Hcc Cellsmentioning
confidence: 99%
“…Although the underlying mechanisms of HCC are not fully understood, the discovery of ferroptosis brings new light to its diagnosis and treatment. Sorafenib, a first-line drug with multikinase inhibitory properties that is used as a reference treatment in advanced HCC, has been investigated intensively to induce ferroptosis in HCC cells [43,44]. Mechanistically, the ferroptosis-inducing effect of sorafenib is due to upregulation of phosphorylation of ferroptosis-related genes or proteins, such as CAD protein (P27708), heavy chain ferritin (FTH1; P02794), and heme oxygenase 1 (HMOX1; 9 Oxidative Medicine and Cellular Longevity P09601) [43].…”
Section: Keyword Analysismentioning
confidence: 99%
“…Sorafenib, a first-line drug with multikinase inhibitory properties that is used as a reference treatment in advanced HCC, has been investigated intensively to induce ferroptosis in HCC cells [43,44]. Mechanistically, the ferroptosis-inducing effect of sorafenib is due to upregulation of phosphorylation of ferroptosis-related genes or proteins, such as CAD protein (P27708), heavy chain ferritin (FTH1; P02794), and heme oxygenase 1 (HMOX1; 9 Oxidative Medicine and Cellular Longevity P09601) [43]. However, sorafenib does not seem to be a bonafide ferroptosis inducer when applied to other cancers [45].…”
Section: Keyword Analysismentioning
confidence: 99%